TELEMEDICINE AS AN OPTION FOR HEALTH SERVICE LIMITATIONS IN COVID-19 PANDEMIC ERA - Bernadette Dian Novita; Sianty Dewi; Evelyn Ongkodjojo; Agatha Christi Palupi; Immanuel Michael; Paul L. Tahalele (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Coronavirus disease 2019 (COVID-19) pandemic era provides a new habit in form of self-quarantine or physical distancing. The recommendation is to delay visits to health facilities if it is not in the emergency condition to slow down the spread of COVID-19 transmission. This study aims to develop a telemedicine system that integrates three main components, namely doctors, patients, and hospital management in Gotong Royong Hospital Surabaya to minimize the transmission of COVID-19 while still provides comprehensive health services. The development of telemedicine service is divided into 3 stages. In the first stage, emergency screening was carried out by developing Frequently Asked Questions (FAQs). The second stage was continued with prototype testing and the last part was improving the system to create a better referral system. Gotong Royong Hospital telemedicine has been active since June 2021, within 2 months, 45 patients are willing to use telemedicine services. The results showed that telemedicine was easily accepted by patients in internal medicine clinic services (p